Measurement uncertainty in biochemical parameters - Telo, Selda; Kaman, Dilara (My University, 2018)
Measurement uncertainty is a quality indicator that is used to show the distribution level of a test result in a laboratory. The aim of this study is to calculate the measurement uncertainty of ten biochemical parameters investigated in our laboratory and compare the obtained values with the permissible total error values (% TEa), which various authorities determine for these tests. The measurement uncertainty of glucose, ALT, AST, urea, creatinine, sodium, potassium, albumin, total protein and total cholesterol were investigated in the biochemical auto analyzer (Siemens Advia 2400). Fifty randomly selected 2 level (low and high) internal quality assessment results and external quality assessment of six-month data, the first six months of 2016, were calculated for each test. Nordtest guide was used for the measurement uncertainty calculation. The measurement uncertainties were calculated as 3.9%, 6.72%, 3.4%, 8.06%, 9.06%, 6.08%, 5.02%, 4.98%, 4.96% and 7.22% for glucose, ALT, AST, urea, creatinine, albumin, total protein and total cholesterol, respectively. The calculated measurement uncertainties were found to be lower than the CLIA’88 and RiLi-BEAK % TEa values, except for sodium. Calculated % TEa values for creatinine, sodium, total protein and albumin were found to be higher than Fraser % TEa values. A test result or a measurement is not sufficiently effective when reliability is not assessed. Laboratories should calculate the measurement uncertainty for each parameter. They should give the results that do not exceed the targeted % TEa values. Clinicians should be informed about the measurement uncertainties so that they consider it while evaluating patient results.
Keywords: Biyokimya ve Moleküler Biyoloji; Tıbbi Laboratuar Teknolojisi; İstatistik ve Olasılık